PEFC electrodes based on carbon black supporting electrocrystallised nanostructured Pt particles. (4th December 2009) - Paoletti, C.; Cemmi, A.; Serra, E.; Pozio, A.
This work is focused on the study of electro-crystallisation of Pt nanostructured particles used as catalyst on carbon black support for polymer electrolyte fuel cells electrodes. Electrochemical single and multiple pulse galvanostatic depositions have been applied defining the best operational parameters leading to a highly nanostructured electro-catalysts morphology. Electrochemical measurements such as cyclic voltammetries have been carried out in order to determine the electrochemical active surface together with morphological analysis by means of scanning electron microscopy. The influence of electro-deposition parameters on the Pt loading have been studied and optimised. The investigated materials have been then characterised by means of polarisation curves. The electrodeposited catalyst cathodes present performances and maximum specific power density values similar or better than those of standard E-TEK electrode, prepared by conventional powder-type technique. These results strongly encourage the implementation of cathodes obtained by electro-deposition in a real-world device.